Motivational profile quality players handball - Alfonso Martínez Moreno (Federación Extremeña de Balonmano; University of Extremadura, 2017)
In the sport context, elite category, it is necessary to know all the factors, which in one way or another, affect the athletes throughout the different competitions. The object of study is to know the motivational profile of elite handball players. The sample consisted of 495 players, of whom 47.8% were boys and 52.2% girls, their ages ranged from 12 to 16 years, with an average of 13.8 years (dt = 1.0). Descriptive statistical analyzes of the sample, absolute and relative frequencies were performed for the qualitative variables and for the quantitative values minimum, maximum, mean, standard deviation, Cronbach's alpha. Correlation between variables, with the Pearson correlation coefficient. The MANCOVA test was performed to determine if there were differences between the dimensions of the questionnaire, according to age and years of practice. The results reveal that handball players elite category of the sample object of study have mainly intrinsic motivation, achieving high scores on general motivation, motivation achievement and motivation stimulation. In addition to moderately high values in introjected regulation and very low values in demotivation.